1976
DOI: 10.1002/food.19760200302
|View full text |Cite
|
Sign up to set email alerts
|

Volatile sulfur compounds contributing to meat flavour. Part. I. Components identified in boiled meat

Abstract: Volatile sulfur compounds from 3 samples of boiled meat (Longissimus dorsi and shoulder meat) have been isolated, separated from the whole flavour complex by mercuric chloride precipitation, regenerated, and examined by gas chromatography. Identification has been carried through by determining Kovats-indices on 4 gas chromatographic columns of different polarity. 29 sulfur compounds have been identified with high certainty, 10 tentitatively. Among 17 thiols, 8 sulfides, 7 disulfides and trisulfides, and 7 hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…These results confirm previous observations that the formation of furyl and thienyl sulphides and disulphides is extremely pH dependent, with maximum formation at low pH values 7,8,12,16,17,21,22,23,24 . The thiols identified included three furanthiols (2-methyl-3-furanthiol [19], 2-methyl-4,5-dihydro-3-furanthiol [36], 2-furylmethanethiol [29]) and three thiophenethiols (2-or 3-thiophenethiol [37] The compounds 19 and 36 were probably formed in the reaction of hydrogen sulphide (Strecker degradation product of cysteine) with 4-hydroxy-5-methyl-3(2H)-furanone (a dehydration product of ribose or 5'-IMP) or other pentose dehydration products 13,25 . 2-Furylmethanethiol [29] was probably formed by the reaction of hydrogen sulphide with 2-furfural, another ribose and 5'-IMP breakdown product 26 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These results confirm previous observations that the formation of furyl and thienyl sulphides and disulphides is extremely pH dependent, with maximum formation at low pH values 7,8,12,16,17,21,22,23,24 . The thiols identified included three furanthiols (2-methyl-3-furanthiol [19], 2-methyl-4,5-dihydro-3-furanthiol [36], 2-furylmethanethiol [29]) and three thiophenethiols (2-or 3-thiophenethiol [37] The compounds 19 and 36 were probably formed in the reaction of hydrogen sulphide (Strecker degradation product of cysteine) with 4-hydroxy-5-methyl-3(2H)-furanone (a dehydration product of ribose or 5'-IMP) or other pentose dehydration products 13,25 . 2-Furylmethanethiol [29] was probably formed by the reaction of hydrogen sulphide with 2-furfural, another ribose and 5'-IMP breakdown product 26 .…”
mentioning
confidence: 99%
“…10,13 , ribose/cysteine 4 , cystine/thiamine/glutamate/ascorbic acid 30,31 . Also [19] has been reported together with 2-methyl-4,5-dihydro-3-furanthiol [36] and 2-methyl-3-thiophenethiol [50], in the volatiles of thermally degraded thiamine 32 . The presence of thiol substituted furans and thiophenes, such as compounds (19, 29, 36, 37, 50, 54), gave rise to a number of important disulphides in the reaction mixtures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The VSCC were analyzed by method [3] Silicon OV-17, Triton X-305 and polyethylene glycol lo00 (PEG-1000) stationary phases on 80-100 mesh Chromosorb W-AW/DMCS. The column temperature was 130 "C, nitrogen of high purity was used as carrier gas (20 ml/min).…”
Section: Gas Chromatographic Analysismentioning
confidence: 99%
“…8) 2FM, which has an intense, roasted, coffee-like aroma, was first identified in roasted coffee. It has been reported to be an important aroma component in such foods as roasted meat [8][9][10] and white wine. 11) The odor threshold was reported to be 0.4 ng/L in a model hydroalcoholic solution by Tominaga et al 12) Shibamoto and Russell 13) have reported the formation of 2FM from furural in the presence of cysteine by an amino-carbonyl reaction, and Blanchard et al 14) have reported that 2FM was formed from furfural in white wine by yeast.…”
mentioning
confidence: 99%